A novel WWTR1:AFF2 fusion in an intra‐abdominal soft tissue sarcoma with associated endometriosis. Issue 8 (26th April 2022) - Dashti, Nooshin K.; Dermawan, Josephine K.; Schoolmeester, J. Kenneth; Halling, Kevin C.; Antonescu, Cristina R.
Abstract: Application of molecular testing in clinical practice has led to significant advances in the classification of soft tissue sarcomas. Despite remarkable progress, there are still challenging cases that remain unclassified. In this study, we present an unusual spindle cell sarcoma arising in the abdominal cavity of a 37‐year‐old female. An extensive panel of immunostains was nonspecific for a line of differentiation and the tumor was subjected to targeted RNA sequencing for further classification. The findings showed a novel WWTR1::AFF2 fusion, which was further confirmed by break‐apart FISH analysis for WWTR1 gene rearrangement. The tumor was attached to the wall of sigmoid colon and showed a highly cellular proliferation of plump spindle to epithelioid cells arranged in intersecting fascicles. Areas of extensive endometriosis were identified adjacent to the tumor. The immunoprofile was significant for reactivity with desmin, calponin, WT‐1, ER, and PR, while negative for CD10, SMA, caldesmon, pan‐keratin, ALK, CD117, and S100. The patient is alive and well after 11 months of follow‐up. The exact histogenesis of this sarcoma remains unclear, however, the presence of adjacent endometriosis and coexpression of WT1/ER/PR raises the possibility of an unusual endometrioid stromal sarcoma, occurring outside the GYN tract. Additional cases are needed to establish the recurrent potential of this fusion event and to better define its pathogenesis and clinical behavior.